Jamaica : Financial Infrastructure Technical Note - World Bank; International Monetary Fund (Washington, DC, 2015)
Financial infrastructure is the underlying foundation of a country’s financial system. It is comprised of all institutions, information, technologies, rules, and standards which enable financial intermediation. The quality of a country’s financial infrastructure determines the efficiency of intermediation, the ability of lenders to evaluate risk and of borrowers to obtain credit, insurance, and other financial products at competitive terms. This report covers two dimensions of Jamaica’s financial infrastructure: 1) payments, remittances, and securities settlement systems, and; 2) credit reporting systems. This technical note does not provide a detailed assessment of individual payments system in the form of a Report on Observance of Standards and Codes (ROSC), but uses the framework of international standards for carrying out a detailed analysis of the existing systems in Jamaica, including the Committee on Payment and Settlement Systems (CPSS) and International Organization of Securities Commissions (IOSCO) Principles for Financial Markets Infrastructure (PFMIs), the CPSS General Guidance for National Payment System Development, the CPSS-World Bank General Principles on International Remittance Services (GPs), the World Bank General Principles for credit reporting and related methodologies. The information used in the assessment includes relevant national laws, regulations, rules and procedures governing the systems and other available material.